ALTERNATIF PEMBELAJARAN MAHARAH QIRA’AH DENGAN KISAH-KISAH DALAM AL-QUR’AN - A. Syahid Robbani; Ahmad Muzayyan Haqqy (El-Tsaqafah : Jurnal Jurusan PBA, 2021)
To realize the effective learning of reading skills, of course, it takesmedia or good learning materials. That way, learning of reading skills willnot feel boring for teachers or students. One of the alternatives that can beused in learning of reading skills is the stories in the Qur’an that are full ofeducational values. This research aims to find alternative learning of readingskills with stories in the Qur’an. This research is a type of library research.The results of this study show that with perfection and privilege in terms oflanguage that the Qur’an has, allows everyone to delve into this especially inArabic learning, especially reading skills. This can be applied in the learningof reading skills by practicing reading (converting the symbol of writing intosound) and understand what is in the reading with the stories in the Qur’an.Both aspects are very important in reading skills. Among the stories in theQur’an that can be used as an alternative in the learning of reading skills isthe story of the patience of the prophet ‘Ayyub in surah Al-Anbiya’ verses83-84, the story of the obedience of the prophet Ibrahim and the prophetIshmael in surah As-Shaffat verses 100-111, the story of the prophet Musawho helped two women drink his cattle in surah Al-Qashash verses 21-24 andthe story of Qarun who was so arrogant that the earth was swallowed upin surah Al-Qashash verses 76-86. Other stories contained in the Qur’an canalso still be used as the alternative learning of reading skills while sticking tothe goal of learning to be achieved.